Postindian aesthetics : affirming indigenous literary sovereignty - Warrior, Robert Allen; Jacobs, Connie A., 1944-; Barker, Debra K. S., 1954- (Book collections on Project MUSE., 2022)
"Postindian Aesthetics is a collection of critical, cutting-edge essays on a new generation of Indigenous writers who are creatively and powerfully contributing to a thriving Indigenous literary canon that is redefining the parameters of Indigenous literary aesthetics"--